MEMPERTAHANKAN KEBERLANJUTAN PERIKANAN PUKAT CINCIN DI PULAU AMBON - Barbara Grace Hutubessy; Revaldo Nanlessy; Selfie Sangadji; Julian Tuhumury (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2021)
Community outreach regarding sustainability of purse seine fishery aims to refresh fishers’ knowledge on the impact of purse seine on the small pelagic resources in Ambon waters. The steps of this activity were started with observation, followed by assessment on the results and continued with community outreach focusing to fishers from Laha Village, Ambon City. The catch of purse seine was composed by Sardine (Sardinella spp), Scads (Decapterus spp and Selar crumenophthalmus), and Indian Mackerel (Rastrelliger kanagurta). Based on the length-frequency of catch, only Indian Mackerel was categorized as undersized (the legal size is 21.7 cm). It is suggested to fishers to lively return several small fish of Indian Mackerel back to ocean. This action will provide an opportunity for the fish to reach reproduction size and reproduce sustaining its population. Fishers agreed to return the fish lively in order to sustain the population of Indian Mackerel. Therefore, monitoring to the sustainability of small pelagic fishes should be continued.